STRATEGI MEDIA RELATIONS DI ERA DIGITAL DALAM MEMPERTAHANKAN CITRA PERUSAHAAN - Vincentius Febrio Berluscony; Nurjanah (Program Studi Komunikasi dan Penyiaran Islam, 2026)
This study examines the media relations strategies implemented by PT Perkebunan Nusantara IV Regional III (PTPN IV Regional III) to maintain its corporate image in the digital era. The analysis primarily focuses on two key elements: the media monitoring and news scoring system as an instrument for reputation evaluation, and the mechanism of publication synergy through partner media networks. This study employs a descriptive qualitative method utilizing participatory observation and document analysis. The research was conducted during the ”Magang Berdampak (Diktisaintek)” internship program at the Public Relations Division of PTPN IV Regional III from January 21 to May 22, 2026. The findings indicate that the company's media relations strategy operates on three pillars: (1) the production of creative content for corporate visual branding; (2) a sentiment-based news scoring system (positive, neutral, negative) drawing on Coombs' (2007) signal detection concept as an early detection mechanism for reputational crises; and (3) strategic partnerships with 13 local and national media outlets, fostering a mutually beneficial relationship between brand exposure and news credibility. Quantitative data from the scoring recapitulation demonstrates a significant upward trend, increasing from 67,270 points (February 2026) to 258,445 points (May 2026), which indicates the effectiveness of the executed communication strategies. This study contributes to the understanding of Public Relations practices in agribusiness State-Owned Enterprises (SOEs) during the digital era, particularly regarding the integration of Agenda Setting Theory, Signal Detection, and Image Theory as a foundation for adaptive reputation management